Theater Performance Analysis Forbidden from Singing in Bath Room by Seno Gumira Ajidarma Theater Had Study Program in Indonesian Language and Literature Education Trunojoyo Madura University (Carles Sanders Pearce Semiotic Study) - Amil, Ahmad Jami’ul (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2020)
This research is descriptive qualitative research that examines theatrical performances of scripts. It is forbidden to sing in the bathroom. The work of Seno GumiraAjiDarma is the study of semiotic carlesanderspearce. The formulation of the problem in this research is how the study of semiotics in the tetater show had once been conducted by the PBSI Study Program using the study of semiotic carles sanders Pearce. Data collection techniques using documentation techniques, note, and see. The analysis technique used is reducing data, promising data, and verifying data. From the results of the study concluded that the semiotics that appear on signs and markers in the form of symbols are the dance of the bathroom, sound, and the shadow of the bathroom. The index aspect is in the form of actor actions in the form of exoticism, anxiety, admiration, exoticism, and the imagination of the actor. The iconic aspect is shown in one of the events, namely the social environment in the form of a house, bathroom, and boarding house.